FACTORS AFFECTING FIRM VALUE THROUGH CAPITAL STRUCTURE AS A MEDIATION VARIABLE - Huanency, Amelia; Wijaya, Henryanto (International Journal of Application on Economics and Business, 2023)
This study aimed to determine the effect of profitability, liquidity, firm size and asset structure on firm value with capital structure as mediating variable in manufacturing companies listed on Indonesia Stock Exchange in the year of 2018-2020. 72 manufacturing companies were taken as the samples and the data was taken by purposive sampling method. Then, the data was analyzed by using the Partial Least Square method with the SmartPLS 3.3.3 application. The results showed that profitability, liquidity, firm size, and asset structure have a positive and significant effect on firm value. Meanwhile, profitability, liquidity and asset structure have a negative and insignificant effect on capital structure. Then, firm size has a positive and insignificant effect on capital structure. Moreover, capital structure cannot mediate the effect of profitability, liquidity, firm size, and asset structure on firm value.